The Nexus Between Air Pollution and Outward Foreign Direct Investment - Qian Zhao; Chi-Wei Su (SAGE Open, 2023)
This study examines the causal relationship between air pollution ( AP ) and outward foreign direct investment ( OFDI ) in China by applying the bootstrap rolling-window full- and subsample Granger causality test in a sample from 2013 to 2022. We find that AP negatively influenced OFDI in 2016, while this influence became positive at the end of 2019. The results confirm the coexistence of the pollution haven hypothesis, factor endowment hypothesis, and Porter hypothesis. In turn, OFDI negatively influenced AP in 2019, which proves the “composition effect” and “technique effect,” implying that OFDI brings better air quality by optimizing the economic structure and promoting green technology. However, this influence became positive in 2020, which is consistent with the “scale effect,” indicating that OFDI worsens air quality by expanding production. This research provides insights for the government to coordinate OFDI growth and carbon neutralization to achieve sustainable development. It also has implications for firms to reduce environmental costs through OFDI .